Aerosol radiometric properties at Western Spain (Cáceres station). (12th May 2014) - Obregón, M. A.; Serrano, A.; Cancillo, M. L.; Cachorro, V. E.; Toledano, C.
ABSTRACT This paper analyses the radiometric properties of aerosol column over Western Spain. It is based on 7‐year data series of aerosol parameters at the AERONET Cáceres station (Spain) as measured by CIMEL sun‐photometers. The study period extends along almost 7 years: from July 2005 to June 2012. The paper aims at analysing the temporal evolution, mean values and spectral dependence of some fundamental aerosol parameters such as aerosol optical depth (τ), Ångström parameter (α), single scattering albedo (ω), asymmetry parameter (g) and volume size distribution (dV dlogr−1); and their relationship with the most frequent air masses that arrive at Western Spain. Mean values correspond to aerosols of small size and low concentration (mean τ500 = 0.11; mean α = 1.38). In fact, 50% of days correspond to 'continental‐clean' type. However, there is a certain variability of conditions, with more than 25% of medium and high turbidity cases with τ500 higher than 0.20. These episodes of high turbidity occur more frequently in August and September and are usually due to the influence of desert‐dust aerosol, biomass burning, continental aerosol, or a mixture of them. The analysis of the all basic and derived aerosol parameters is explained by the main influences: continental location, exposed to maritime aerosols coming from the Atlantic Ocean, and affected by Saharan dust intrusions.